Spectral Change Based Optical Sensors - Eliáš, Josef (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This paper is focused on optical sensors based on spectral characteristics change. Optical sensors are widely used for industrial, robust and noise proof measurement. There are measurement techniques for mechanical tension, temperature, pressure, displacement, vibration and so on. This article provides brief description of selected optical sensors based on Fabry-Perot and fiber Bragg grating principle. The article includes basic sensor description, theory of operation and measurement setup and expected measurement ranges and resolutions.
Keywords: Fiber optic sensors; Fabry-Perot interferometer; Fiber Bragg Grating; Measurement